Gender double standards in young people attending sexual health services in Northern Thailand - Arunrat Tangmunkongvorakul (2018)
Concern about the sexual and reproductive health of young people has been mounting recently in Thailand. Unequal gender relations have a considerable influence on the lives of young people, especially young women, yet few studies have explored the ways in which they have impacted on provision of sexual health care. Drawing upon data from a qualitative study in Northern Thailand, this paper explores the views and experiences of young people in seeking health care, highlighting the kinds of gender double standards and power imbalances that may pose obstacles to their use of sexual and reproductive health services. Findings reveal the vulnerability of sexually active young women in seeking support and care from partners, parents, and service providers. Those who experience adverse outcomes of sexual activity, such as unwanted pregnancy or infection, report facing indifference, victim blaming, or the threat of abandonment by their partners. Because of their fear of disclosure to their parents and communities, of their sexual activity, they opt for clandestine and unsafe abortion and seek the counsel of peers and drugstores rather than parents and providers. At the service provider level, young women report facing threatening and judgemental attitudes, indifferent counselling, and possible violation of confidentiality. This is in marked contrast to the treatment of young men, who generally meet with a more sympathetic and accepting response. © 2005 Taylor & Francis Group Ltd.